Edukasi Hipertensi, Pemeriksaan Tekanan Darah Dan Senam Anti Hipertensi Pada Lansia Di Desa Mantawa - I Gede Restawan; Janice Sepang; Imelda Kantohe; Sri Purwiningsih (Jurnal Abdimas Kesehatan (JAK), 2026)
Hypertension remains a significant health problem worldwide, including in Indonesia. Prevention and regular blood pressure checks, as well as complementary therapies such as antihypertensive exercises, are needed to control this condition. The purpose of this community service is to increase elderly knowledge about hypertension and antihypertensive exercises as an effort to prevent and control blood pressure. The methods used in this activity include blood pressure checks, counseling on hypertension, and demonstration of antihypertensive exercises. The activity was carried out in Mantawa Village, precisely at the Balai Banjar Dusun III on December 16, 2024, attended by 42 elderly people (28 women and 14 men). The examination results showed that the systolic pressure before the antihypertensive exercise was 178.86 mmHg, which decreased to 169.89 mmHg after the exercise, while the diastolic pressure decreased from 102.75 mmHg to 96.02 mmHg. In addition, the pretest and posttest results showed an increase in elderly knowledge about hypertension from 42.86% to 90.48%, as well as an understanding of the importance of antihypertensive exercises from 28.57% to 80.95%. This activity succeeded in increasing the knowledge and awareness of the elderly about hypertension and antihypertensive exercises, and showed a significant decrease in blood pressure. It is hoped that similar activities can be continued periodically to improve the health of the elderly and encourage them to be more active in maintaining health through antihypertensive exercises and routine blood pressure checks.